Neonatal mortality and outcome at the end of the first year of life in early onset urea cycle disorders—review and meta-analysis of observational studies published over more than 35 years - Burgard, Peter; Kölker, Stefan; Haege, Gisela; Lindner, Martin; Hoffmann, Georg F. (Journal of inherited metabolic disease, 2016)
Background For urea cycle disorders (UCD), proportions and mortality of early onset (EO) patients, as well as outcome at one year of life show large variability. We aimed to integrate available evidence to create benchmarks for new diagnostic and therapeutic strategies. Methods Medline search for reports published between 1978 and Dec 22, 2014 was completed by hand search. Random effects meta-analysis was done for four UCDs, deficiency of carbamylphosphate synthetase 1 (CPS1D), male/female ornithine transcarbamylase (OTCDm/f), argininosuccinate synthetase (ASSD) and lyase (ASLD). Effects of publication year and geographic area were analysed by meta-regression. Results Twenty-four publications report onset time (n = 1542 patients), survival of EO (n = 665 patients) and outcome at one year of life (n = 172 patients). Proportions for EO manifestation (95 % confidence interval) were: CPS1D = 0.75 (0.61;0.88); OTCDm = 0.52 (0.39;0.65); OTCDf = 0.07 (0.03;0.11); ASSD = 0.65 (0.57;0.73); ASLD = 0.60 (0.44;0.77); for surviving EO patients: CPS1D = 0.64 (0.50;0.79); OTCDm = 0.40 (0.16;0.64); OTCDf = 0.57 (0.29;0.85); ASSD = 0.67 (0.48;0.86); ASLD = 0.81 (0.68;0.94); and for normal outcome at one year for survivors: CPS1D = 0.20 (0.07;0.38); OTCDm = 0.15 (0.00;0.39); OTCDf no data; ASSD = 0.36 (0.13;0.60); ASLD = 0.36 (0.17;0.58). Between study variation was large. Year of publication had no effect. Studies from Europe showed lower survival rates than those from Japan or USA. Conclusions UCDs, except for OTCDf, have high risks of EO disease manifestation and, except for ASLD, of neonatal death. No improvement of survival was observed over more than three decades. Geographic variation remains to be explained. This comprehensive description of the natural history of EO UCDs should be considered by scientists, clinicians, health policy makers and guideline developers.
First published: 03 December 2015
Gesehen am 25.05.2020